The Attitudes of Pete Program Applicants Towards Information and Communication Technologies - Varga, Attila; Bácsné Bába, Éva; Ráthonyi, Gergely; Müller, Anetta (Applied Studies in Agribusiness and Commerce, 2019)
As information and communication technology has permeated all aspects of life education cannot be considered an exception either. The schools of the 21st century require the use of the latest digital devices whose effectiveness is greatly determined by the motivation, ICT-related attitude, and the respective competences of teachers managing and directing the given teaching and learning process. Since P.E. also requires the use of information and communication devices it would be crucial that prospective teachers develop a positive attitude toward such equipment. The present research aims at exploring the attitudes of students applying to P.E. teacher programs at the Eszterházy Károly University toward such instruments and approaches. Additional research objectives include the exploration of potential correlation between the sex of the applicants and the respective attitudes. Our inquiry utilized the questionnaire method and the computer-based attitude scale was completed by a sample of 130 applicants in the 2016/2017 and the 2017/2018 academic years.  Our research concluded that both men and women maintain a positive attitude toward the use of digital devices, or the tools of information and communication technology. Students representing both sexes consider the computer as a valuable learning device promoting the efficiency of the knowledge acquisition process. Furthermore, a significantly greater proportion of male respondents stated that they were capable of repairing computer problems emerging during use than that of their female counterparts. At the same time men are less apprehensive to use computers during instruction and this attitude appears to be an indispensable requirement for the application of ICT devices in class. The research can contribute to a deeper exploration of the given field along with performing a gap filling function as such examination has not yet been conducted among applicants to P.E. programs provided by higher education institutions in Hungary.JEL Classification: Z2, I23